Antibacterial Activity of Various Solvent Extracts of Some Selected Medicinal Plants Present in Jaffna Peninsula - Viviyan, S.; Niranjan, K.; Tharmila, S.; Christy Jeyaseelan, E. (International Journal of Pharmaceutical & Biological Archives, 2012)
Medicinal plants have been very intensively screened for their bioactivity in order to treat various disease and disorders in human. In this study some common medicinal plants (Cassia fistula, Heliotropium indicum, Mimosa pudica, Rhinacanthus nasutus, Pongamia pinnata and Vernonia zeylanica) available in Jaffna peninsula, Sri Lanka, were tested for their antibacterial activity. Leaf powders of above plants were sequentially extracted with petroleum ether, ethyl acetate, ethanol and water respectively. The dried extracts were tested for their antibacterial activity against Staphylococcus aureus (NCTC 6571) and Escherichia coli (ATCC 25922) by agar well diffusion method. The yield percentage was relatively high in tested polar solvents than tested non polar or low polar solvents. Among the tested extracts, aqueous extract of Mimosa pudica and ethyl acetate extract of Cassia fistula revealed significantly higher inhibition against S. aureus and E. coli respectively. The test extracts of Mimosa pudica showed interesting results, all of its extracts were able to inhibit both S. aureus and E. coli. Most of the tested extracts could be used for further screening of specific bioactive compounds which responsible for their antibacterial activity
Keywords: Medicinal plants; Sequential extraction; Antibacterial activity; Well diffusion method